SOCIAL DEVELOPMENT OF PERSONNEL IN THE CONDITIONS OF INNOVATIVE ECONOMY AS A FACTOR OF INCREASING THE LEVEL OF LIFE QUALITY - N. I. Laas; I. A. Romanova; E. V. Gurova (Вестник университета)
The importance of the social development of personnel in innovative economy as a decisive factor in the stability of society and improving the quality of life of both workers themselves and the entire population of the country has been defined. It has been shown that social development of staff in the organization contributes to the improvement of social and labor relations through interaction of the parties of social partnership based on the principle of tripartite cooperation and “tripartism”, and also contributes to the full development of the potential of employees and their professional competences. The main directions of social development of personnel included in the social policy of the organization have been determined in the paper. As a result of the research, priority role of cash payments and guarantees in the organization’s social responsibility strategy have been identified. At the same time, the main principle in the development of policy aimed at social development of staff should be targeted consideration of the needs of employees. The principle of targeting to determine the level of staff satisfaction should be the main one for evaluating the effectiveness of work in this direction. In addition, the authors point to the need to use modeling and forecasting the prospects of social innovations in order to achieve sustainable development in the long term.